How the crystal structure and phase segregation of Au–Fe alloy nanoparticles are ruled by the molar fraction and size. Issue 35 (23rd August 2018) - Tymoczko, Anna; Kamp, Marius; Prymak, Oleg; Rehbock, Christoph; Jakobi, Jurij; Schürmann, Ulrich; Kienle, Lorenz; Barcikowski, Stephan
Abstract : An ultrastructure of Au–Fe alloy nanoparticles is predefined by the Au : Fe target composition under certain size restrictions as predicted by theoretical modeling. Abstract : The application of an Au–Fe nanoalloy is determined by its internal phase structure. Our experimental and theoretical findings explain how the prevalence of either a core–shell or a disordered solid solution structure is ruled by the target composition and the particle diameter. Furthermore, we found metastable phases not predefined by the bulk phase diagram.